RENAL HISTOPATHOLOGICAL AND MCP-1 MODULATION IN MALE RAT (Rattus norvigicaus) FOLLOWING REPEATED TiO2 NPs INTRATRACHEAL INSTILLATION - Fatimah A. Jasim; Dhamia K. Suker (Basrah Journal of Veterinary Research)
The rapidly expanding field of nanotechnology is becoming a possible source for humanexposure to nanoparticles. Titanium dioxide nanoparticles (TiO2-NPs) is one of an importantnanoparticle which has been widely manufactured in developed processes for several years. Theaim of this study was to investigate the effects of TiO2-NPs on some biochemical parameters andthe renal histopathology alterations in adult Wistar rats. 63 male rats were used and treated withdifferent doses (0.5, 5, 50, 1.5, 15, 150 mg/kg) of TiO2-NPs (21 nm) twice a week for 4 weeks.Each group separated into three subgroups then sacrificed at 4 days, month and 3 months postintratracheal instillation. The IL-10 and MCP-1 estimation in BALF and histopathologicalexamination of kidney were done. The results showed serve histological alteration in renal elementspost 4 days post-instillation, which got an increase in a month post instillation as the concentrationof MCP-1 and IL-10 increased in BAlF and in lung tissues homogenate. The histopathologicalexamination revealed decreasing in glomeruli number in cortex of the kidneys with hemorrhage andinflammatory cells infiltration at 4 days post-instillation while after a month of instillation, thechanges like swelling, dilatation of Bowman's capsule and degeneration changes in renal tubuleswere observed. At 3 months post-instillation, some regeneration in renal elements were observed.